Mathematical models for Isoptera (Insecta) mound growth - Buschini, M. L. T.; Abuabara, M. A. P. [UNESP]; Petrere-Jr, Miguel [UNESP] (Instituto Internacional de Ecologia, 2008)
Nessa pesquisa, propusemos dois modelos matemáticos derivados da curva de Von Bertalanffy para o crescimento dos ninhos de Isoptera; um específico para Nasutitermes coxipoensis; e outro mais geral. A altura média e o diâmetro médio de dez colônias pequenas foram medidas a cada mês, de abril de 1995 a abril de 1996. Através desses dados, foi calculado o volume mensal de cada colônia. Posteriormente os crescimentos em altura e volume foram estimados e os modelos propostos.

In this research we proposed two mathematical models for Isoptera mound growth derived from the Von Bertalanffy growth curve, one appropriated for Nasutitermes coxipoensis, and a more general formulation. The mean height and the mean diameter of ten small colonies were measured each month for twelve months, from April, 1995 to April, 1996. Through these data, the monthly volumes were calculated for each of them. Then the growth in height and in volume was estimated and the models proposed.
Modelos matemáticos para crescimento dos ninhos de Isoptera (Insecta)
Keywords: Nasutiternes coxipoensis; Isoptera; Insecta; crescimento de ninhos; Nasutitermes coxipoensis; Isoptera; Insecta; mound growth